THE PSYCHOLOGICAL STRUGGLE IN THE SONG “GIVE US CHILDHOOD” BY REMY BANDALI - Anshar Zulhelmi; Dava Diah Pamusti (An-Nahdah Al-'Arabiyah, 2022)
Abstract Literature is a form of art that expresses human thoughts and feelings through the beauty of language, the originality of ideas and the depth of the message. Where literary psychology is a literary study that includes works as psychological creativity. The researchers were interested in analyzing the song "Give Us Childhood" by Remy Bandali using the literary psychology method, and the reason for the analysis from the perspective of literary psychology is that it found an internal conflict experienced by the characters in the song. The research method used in this study is descriptive analysis, which describes the forms of internal structures of Palestinian children in the lyrics of the song "Give Us Childhood" written by Remy Bandali. As for the data in this study, it is journals, articles and research related to the research